Modeling study of the hydrodynamic arc breaking mechanism in BEAM. Issue 1 (2018) - Zhao, Wansheng; Gu, Lin; Zhang, Fawang; Rajurkar, K.P.
Abstract: Blasting erosion arc machining (BEAM) utilizes thermal effect of the arc rather than spark to remove workpiece material. This paper investigates the expansion and distortion rules of the discharge channel based on the analysis of high speed photography and the micrographs of craters to study mechanism of BEAM. Based on these investigations, a thermal finite element model is developed. Then the temperature distributions in workpieces, both with and without flushing, are obtained. The comparisons of the obtained temperature distributions explain the formation of the trailing crater and the effect of hydrodynamic arc breaking mechanism on the efficiency of BEAM.